Comparison of Topical Metformin 40% Cream with Triple Combination Cream in Treatment of Melasma in Females - Aulfet Aied Shnain AL-Yassery; Rufaida Mahmood Muhi (Karbala Journal of Medicine, 2025)
Background: Melasma is a common acquired illness characterized by an outbreak of brown and often symmetrical hyperpigmented patches on frequently sun-exposed face areas. Its treatment is important because it affects the patient’s appearance. Although topical treatments are used several times daily and for several months, they partially eliminate the lesions. This study aimed to assess and compare the efficacy of topical metformin with triple combination cream (TCC) in treating melasma. Methods: A randomized controlled trial was carried out at the clinic of the Department of Dermatology in Imam Hassan Teaching Hospital in Karbala. Fifty females with melasma were selected. They were divided equally (25 patients) into two groups. Group A was given topical metformin 40% once daily for 2 months, and Group B was given TCC for 2 months. The patients were followed up during the treatment period. Results: The mean age of group A was 35.06± 6.46 years, and in group B it was 34.02 ± 5.37 years. The decrease in Melasma Area and Severity Index (MASI) score was more among the metformin group (A) at 2 weeks with statically significant (p= 0.025) and a high percent of satisfaction (72%), while at 8 weeks there was no statistical difference in MASI score and the satisfaction was 88% in the metformin group. Conclusions: Melasma can be treated safely and novelly with topical metformin, which is as effective as TCC. Keywords: metformin, melasma, triple combination